The significance of relational continuity of care for Māori patient engagement with predominantly non‐Māori doctors: findings from a qualitative study. (3rd September 2015) - Reid, Jennifer; Cormack, Donna; Crowe, Marie
Abstract: Objective : This qualitative study explored self‐reported experiences of primary healthcare among a sample of urban Māori adults. This paper specifically focuses on the theme of relational continuity of care identified in participant discussions of access and engagement with their predominantly non‐Māori general practitioners (GPs). Methods : The study involved a purposively selected subsample (n=42) of the Christchurch Māori cohort of the Hauora Manawa Community Heart Study (n=244). Participants took part in in‐depth interviews, which were transcribed and analysed thematically. Results : Analysis identified compromised access to a preferred GP as a principal barrier to receiving quality and non‐discriminatory care from predominantly non‐Māori clinicians. In contrast to discussions of healthcare provided by usual GPs, episodic encounters with non‐regular clinicians were commonly framed as experiences discouraging utilisation and the perceived value of primary healthcare. Conclusions : Facilitating relational continuity of care for Māori patients and their clinicians may contribute towards mediating determinants of inequality at the clinical interface. Implications : Reducing significant health disparities between Māori and non‐Māori was a key goal of the reconfiguration of primary healthcare in the early 2000s. The role of relational continuity of care in achieving equitable inter‐ethnic health outcomes in primary healthcare settings is an important consideration.